A Study on the Applicability of NFT in the Entertainment Industry: Application of the Means-end Chain analysis and Laddering - Jaeseo Choi (International Telecommunications Society (ITS), 2024)
The advancements in digital technology have not only transformed business operations across various industries but also driven rapid changes and innovations within business landscape. Digital technology operates independently of economic development levels, and the emergence of novel technologies enables diverse business to explore new business model (Ali et al., 2020). There has been a movement towards anticipating a paradigm shift in technological frameworks to establish the groundwork for Web 3.0 and to incorporate these changes into business model (Yoo et al., 2022). To keep up with the paradigm shift on the technological front, companies are navigating significant growth in the business domains related to information collection, management, and storage. Moreover, digitalization has recently emerged as a new aspect in information investment, coinciding with the growth (Ali et al., 2020). In the situation of the changing landscape information and communication technology utilization, survival for businesses entails leveraging aspects if the innovation lifecycle. This involves applying new strategies based on it, introducing innovative business model, and harnessing digital technology (Kaijkawa et al., 2022). Non-Fungible Token (NFT) can be regarded as a prime example where the emergence of digital technology has reshaped business approaches for enterprises (Ali et al., 2023).
Keywords: 330; NFT; Means-end Chain analysis; Laddering; Entertainment Industry